2020
DOI: 10.20452/pamw.15669
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medicine among cancer patients

Abstract: RESEARCH LETTER The use of CAM among cancer patients 83 Statistical analysis The analysis was carried out using the IBM SPSS Statistics 26 program (IBM Co., Armonk, New York, United States). The significance level was set at a P value of 0.05. The statistic values for the χ 2 test for data independence were calculated. The Cramer V coefficient was calculated to assess the strength of association. In order to detail the occurring relationships, the z test was used to compare the structure indices (percentage va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Most patients (96.5%) failed to inform their clinicians about the use of anthelmintics for cancer treatment. This result was consistent with that of previous studies [ 13 , 14 ], which showed that a substantial proportion of patients refused to consult their clinicians about alternative therapies. Moreover, patients (3.5%) who informed their clinicians about the therapy reported that they did not receive their support.…”
Section: Discussionsupporting
confidence: 93%
“…Most patients (96.5%) failed to inform their clinicians about the use of anthelmintics for cancer treatment. This result was consistent with that of previous studies [ 13 , 14 ], which showed that a substantial proportion of patients refused to consult their clinicians about alternative therapies. Moreover, patients (3.5%) who informed their clinicians about the therapy reported that they did not receive their support.…”
Section: Discussionsupporting
confidence: 93%
“…In the liter- ature, this result found consistent with studies in which city life increased the frequency of CAM preference, but inconsistent with studies reporting it decreased. 30,31 In this study, when the histopathological tumor types and CAM preference statuses of the patients were examined, it was found that patients with SCLC used CAM at a higher rate (p=0.046). This result was not compatible with the study which reported that tumor type had no effect on the frequency of CAM use.…”
Section: Discussionmentioning
confidence: 68%
“…27 In this study, it was found that patients frequently preferred herbal products, which was consistent with the literature data. 30 With the thought that organic products are harmless and the desire to find healing, there may be a high interest in such CAM methods. At the same time, easy access to such products by patients may increase the frequency of preference for herbal alternative supplements.…”
Section: Discussionmentioning
confidence: 99%
“…According to several cross-sectional surveys, more than one-third of cancer patients in Japan, Poland, and Wales receive unconventional therapies to support their cancer treatments or replace conventional therapies, [ 1 , 2 , 3 ]. This may be explained as follows.…”
Section: Introductionmentioning
confidence: 99%